The Influence of Facebook Social Media on the Sale of Flying Fish (Decapterus spp.) in Sapolohe Village, Bontobahari District, Bulukumba Regency - Nur Fariza Waris; Abd. Wahid; Andi Amri; Arie Syahruni Cangara (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2025)
This study explores the use of social media, especially Facebook, as a marketing tool for mackerel products (Decapterus spp.) in Sapolohe Village. Facebook is one of the first social media known and used by the previous generation. Facebook, with features such as paid advertising, business pages, and community groups, allows sellers to interact directly with potential customers, increase market reach, and strengthen brands. This study aims to determine the marketing strategies implemented by business actors and the influence of the use of Facebook social media in the sale of mackerel. The research used is quantitative descriptive with a census approach, involving 30 fish sellers on Facebook. The results showed that the majority of sellers actively post every day, and 100% of respondents chose to deliver products to the buyer's address. Regression tests showed that the use of Facebook had a significant positive effect on increasing mackerel sales, with a regression coefficient of 0.981 and a p-value of 0.000. These findings indicate that marketing strategies through Facebook are effective and influential in increasing sales and facilitating interaction with customers, as well as providing convenience in the transaction process and product delivery.